School Attachment and Violent Attitudes Preventing Future Violent Behavior Among Youth - Varela, Jorge J. (Journal of interpersonal violence, 2021)
Evidence derived from social information theories support the existence of different underlying cognitive mechanisms guiding violent behavior through life. However, a few studies have examined the contribution of school variables to those cognitive mechanisms, which may help explain violent behavior later in life. The present study examines the relationship between school attachment, violent attitudes, and violent behavior over time in a sample of urban adolescents from the U.S. Midwest. We evaluated the influence of school attachment on violent attitudes and subsequent violent behavior. We used structural equation modeling to test our hypothesis in a sample of 579 participants (54.9% female, 81.3% African American). After controlling for gender and race, our results indicated that the relationship between school attachment and violent behavior over time is mediated by violent attitudes. The instrumentalization of the school context as a learning environment aiming to prevent future violent behavior is also discussed.